CLI-MARK: Weather forecasts, insurance and markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2019)
Some 20 million livestock keepers in the Horn of Africa are threatened by increasingly frequent and severe droughts. These have eroded the pastoralists’ adaptive capacity and resilience to such an extent that almost every drought now results in a humanitarian crisis. A CTA-led project, Enhancing market response to resilience in livestock value chain in Eastern Africa (CLI-MARK), is scaling upmarket mechanisms that increase the adaptive capacity of pastoralists in northern Kenya and southern Ethiopia.